Рекомендации по Перевозке Опасных Грузов - United Nations Economic Commission for Europe (United Nations, 2024)
These Recommendations (Volumes I & II) have been developed by the United Nations Economic and Social Council’s Committee of Experts on the Transport of Dangerous Goods in light of technical progress, the advent of new substances and materials, the exigencies of modern transport systems and, above all, the requirement to ensure the safety of people, property and the environment. They are addressed to governments and international organizations concerned with the regulation of the transport of dangerous goods. They do not apply to the bulk transport of dangerous goods in sea-going or inland navigation bulk carriers or tank-vessels, which is subject to special international or national regulations.